The Role of Teachers and Education Personnel in the Implementation of the Islamic Religious Education Quality Assurance System - Yuyun Yuningsih; Imam Aris Faisal; Romi Ma’ali; Pepen Supendi; M. Nasir; M. Makhrus Ali (BASICA, 2025)
This study aims to analyze the role of teachers and educational staff in the implementation of the Islamic Religious Education quality assurance system at MTs Al-Islamiyah Kotabumi Lampung. The study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers have a strategic role in the implementation of the quality assurance system through lesson planning, evaluation implementation, religious character development, and role models in madrasah life. Educational staff also contribute to supporting a culture of quality through administrative services, infrastructure management, and support for religious programs in schools. Supporting factors for quality implementation include the commitment of the madrasah principal, religious culture, and adequate educational facilities. Meanwhile, obstacles faced include limited learning time, differences in student abilities, and challenges of technological developments and the social environment. Quality strengthening strategies are carried out through improving teacher competency, strengthening religious culture, regular evaluations, and utilizing educational technology. This study emphasizes the importance of collaboration between all elements of the madrasah in realizing an effective and sustainable Islamic Religious Education quality assurance system.